Women in the Struggle for Irish Independence - McKenna, Joseph (McFarland & Company, Inc., Publishers, 2019)
"Women have too often been written out of history. This is especially true in the fight for Irish independence. The women's struggle was three-fold, beginning with the suffragettes' fight to win the vote. Then came the push for fair pay and working conditions. Binding them together became part of the national struggle, first for home rule, then for the establishment of an Irish Republic. The Easter Rising of 1916 brought them together as soldiers of the Republic. Through the terrible years that followed they became the conscience of Republicanism. Following independence, they were betrayed by the men they had served alongside. DeValera and the Catholic Church restricted their roles in society-they were to be wives and mothers without a voice. It was not until Ireland's entry into the European community and the self destruction of a corrupt Church that Irish women were acknowledged for what they had achieved."--Provided by publisher